Associations of cells from both innate and adaptive immunity with lower nerve conduction velocity: the Maastricht Study - Dan Ziegler; Michael Roden; Christian Herder; Haifa Maalmi; Kristiaan Wouters; Jeroen H P M van der Velde; Jos P H Reulen; Werner Mess; Casper G Schalkwijk; Nicolaas C Schaper (BMJ Open Diabetes Research & Care)
Introduction Distal sensorimotor polyneuropathy (DSPN) is common in people with diabetes but is also found in pre-diabetes. Peripheral nerve myelin damage, which can be assessed by reduced nerve conduction velocity (NCV), is an essential feature of DSPN. Emerging evidence indicates that the development of DSPN may involve the activation of the immune system. However, available studies have mainly investigated circulating immune mediators, whereas the role of immune cells remains unclear. Therefore, we aimed to test whether leukocyte subsets are associated with NCV.Research design and methods This cross-sectional study analyzed data from 850 individuals (of whom 252 and 118 had type 2 diabetes and pre-diabetes, respectively) of the Maastricht Study. NCV was measured in the peroneal and tibial motor nerves and the sural sensory nerve and summed to calculate a standardized NCV sum score. Associations between percentages of leukocyte subsets and NCV sum scores were estimated using linear regression models adjusted for demographic, lifestyle, metabolic and clinical covariates.Results After adjustment for covariates, higher percentages of basophils and CD4+ T cells were associated with lower NCV (p=0.014 and p=0.005, respectively). The percentage of CD8+ T cells was positively associated with NCV (p=0.022). These associations were not modified by glucose metabolism status (all pinteraction >0.05). No associations were found for monocytes, eosinophils, neutrophils, lymphocytes, total T cells, Treg cells and B cells.Conclusions The associations of basophils, CD4+ and CD8+ T cells with NCV suggest that cell types from both innate and adaptive immunity may be implicated in the development of DSPN.